118-(7x+16)=7(x+6)+x

Simple and best practice solution for 118-(7x+16)=7(x+6)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 118-(7x+16)=7(x+6)+x equation:


Simplifying
118 + -1(7x + 16) = 7(x + 6) + x

Reorder the terms:
118 + -1(16 + 7x) = 7(x + 6) + x
118 + (16 * -1 + 7x * -1) = 7(x + 6) + x
118 + (-16 + -7x) = 7(x + 6) + x

Combine like terms: 118 + -16 = 102
102 + -7x = 7(x + 6) + x

Reorder the terms:
102 + -7x = 7(6 + x) + x
102 + -7x = (6 * 7 + x * 7) + x
102 + -7x = (42 + 7x) + x

Combine like terms: 7x + x = 8x
102 + -7x = 42 + 8x

Solving
102 + -7x = 42 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
102 + -7x + -8x = 42 + 8x + -8x

Combine like terms: -7x + -8x = -15x
102 + -15x = 42 + 8x + -8x

Combine like terms: 8x + -8x = 0
102 + -15x = 42 + 0
102 + -15x = 42

Add '-102' to each side of the equation.
102 + -102 + -15x = 42 + -102

Combine like terms: 102 + -102 = 0
0 + -15x = 42 + -102
-15x = 42 + -102

Combine like terms: 42 + -102 = -60
-15x = -60

Divide each side by '-15'.
x = 4

Simplifying
x = 4

See similar equations:

| 25x-7-14x+2=23x-4-12x+17 | | 0=0.5x-7 | | -20.4=b+-4.6 | | -14.25+v=-21.55 | | 6x^2-30x+6= | | (4a-3)=(2a+9) | | -12.3=n-24.5 | | (5y-3)=22 | | s*5+36=106 | | 2x^2+1ox-48= | | 10h-28=72 | | 69-13=35 | | 5x-12=x+11 | | 2x+11-5x-13= | | -7.8q+1.6=-62.4-1.4q | | 3x+6y-330=0 | | (2p^6s^8)(s^8)= | | 27.7=20.2+b | | 7/12÷3/4 | | 15x^2+2x-24= | | (7x^2)(-4x^3)(6x^6)= | | N+-10.8=-35.4 | | s*6-28=55 | | x/300=12 | | 0.5x*0.2x=0.125 | | 3/4x5/6= | | (2x+5)=(6x+10) | | 6x^3=-22x+28x^2 | | -21.263+n=-44.464 | | Y-6=43 | | 6y-22=20 | | Logx=-3/2 |

Equations solver categories